2022
DOI: 10.1038/s41598-022-20749-9
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating a pachychoroid and healthy choroid using an unsupervised machine learning approach

Abstract: The purpose of this study was to introduce a new machine learning approach for differentiation of a pachychoroid from a healthy choroid based on enhanced depth-optical coherence tomography (EDI-OCT) imaging. This study included EDI-OCT images of 103 eyes from 82 patients with central serous chorioretinopathy or pachychoroid pigment epitheliopathy, and 103 eyes from 103 age- and sex-matched healthy subjects. Choroidal features including choroidal thickness (CT), choroidal area (CA), Haller layer thickness (HT),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…Research by Devarakonda et al [119] and Srivastava et al [121] demonstrates that incorporating choroidal features significantly enhances model performance in classification tasks. Studies by Jee et al [129] and Mirshahi et al [131] exemplify the importance of choroidal features in AI analysis, aligning with our current understanding of choroidal involvement in various diseases.…”
Section: ) Classification Of Lesions and Vesselssupporting
confidence: 64%
“…Research by Devarakonda et al [119] and Srivastava et al [121] demonstrates that incorporating choroidal features significantly enhances model performance in classification tasks. Studies by Jee et al [129] and Mirshahi et al [131] exemplify the importance of choroidal features in AI analysis, aligning with our current understanding of choroidal involvement in various diseases.…”
Section: ) Classification Of Lesions and Vesselssupporting
confidence: 64%
“…[ 121 , 122 ] Recently, cluster analysis was used to determine salient criteria for CSCR or PPE differentiation from healthy eyes. [ 123 ] Using an unsupervised machine learning technique, these researchers found that the Haller ratio (Haller layer thickness divided by choroidal thickness), choroidal thickness, and CVI were the most important factors for delineation. The Haller ratio was the most valuable single factor, and, along with total choroidal thickness, it was noted that these two values may be the most useful for clinical practice.…”
Section: Resultsmentioning
confidence: 99%
“…The Haller ratio was the most valuable single factor, and, along with total choroidal thickness, it was noted that these two values may be the most useful for clinical practice. [ 123 ]…”
Section: Resultsmentioning
confidence: 99%
“…This method can handle mixed types of variables as well as large datasets. However, it cannot handle missing data [70][71][72][73].…”
Section: Segmentation Analysesmentioning
confidence: 99%